Video documental :biografía del bailarín y poeta Mario Moreno Garibotto - Gavilanes Tamayo, Joel Israel (2017)
Memory is considered as that set of mythologies and images that are rewarded to an opaque past and lacking in objectivity. However, it is through it that political and social processes have other means to be counted and lived, apart from the objective history that is presented to us, spoken by a single voice and by a single resource that is the written word. The images are concurrent allies of memory, timeless and spatial that reveal an interpretation of those facts, reviving them and counting them with different voices and judgments, promulgating an information bank that belongs purely to the collective from which it was born. This work aims to delve into the memories of Mario, an 84-year-old poet whose memories have been witnessed in the construction of a Country, as well as being my way of reviving and interpreting those old experiences of which Mario speaks and Feels as if they had just happened a few months ago.